RELATIONSHIP RELATED TO THE PROTECTION OF TAXPAYERS' RIGHTS AND INTERESTS IN MONITORING THEIR ACTIVITIES - Nizomxonov Elbekxon Erkinxon о‘g‘li (Modern American Journals, 2026)
This article shows existing shortcomings of tax system, in particular, high level of tax burden, availability of many types of taxes, etc, which make the need for reforms in this sector. Therefore, a draft concept of tax system was developed
Keywords: Tax system, tax burden, types of taxes, tax reform, tax concept, tax administration, tax and mandatory payments.